Electrolytic capacitor and manufacturing method

By combining conductive polymer and flexible viscous crystallization in the electrolyte layer of the electrolytic capacitor and controlling its adhesion ratio, the problem that capacitance and ESR in the conductive polymer electrolytic capacitor is difficult to optimize at the same time, and the effects of high capacitance, low ESR and good electrostatic capacitance are achieved.

CN119604957APending Publication Date: 2025-03-11NIPPON CHEMI CON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056336.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-05
Filing Date
2023-08-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In electrolytic capacitors using conductive polymers, it is difficult to achieve both good capacitance and low equivalent series resistance (ESR) and good electrostatic capacitance.

Method used

By including conductive polymer and flexible adhesive crystals in the electrolyte layer of the electrolytic capacitor, the amount of conductive polymer is 1 during the manufacturing process, and the amount of flexible adhesive crystals is adhered to twice or more and 12 times or less based on weight ratio to form an electrolyte layer.

Benefits of technology

In the case of using conductive polymers, a good capacitance is achieved, while reducing ESR and improving the capacitance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257078590000131
    Figure BDA0005257078590000131
  • Figure BDA0005257078590000132
    Figure BDA0005257078590000132
  • Figure BDA0005257078590000133
    Figure BDA0005257078590000133
Patent Text Reader

Abstract

The present invention provides an electrolytic capacitor using a conductive polymer and having better capacitance, and a method for manufacturing the electrolytic capacitor. The electrolytic capacitor includes an electrolyte layer including a conductive polymer and a soft viscous crystal. The method for manufacturing the electrolytic capacitor includes an electrolyte layer forming step of forming an electrolyte layer between the pair of electrodes. The electrolyte formation step comprises: a polymer adhesion step for adhering a conductive polymer to one or both of the pair of electrodes; and a soft viscous crystal adhesion step for adhering soft viscous crystals to one or both of the pair of electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrolytic capacitor and a manufacturing method thereof. Background Art

[0002] Electrolytic capacitors include valve metals such as tantalum or aluminum as anode foil and cathode foil. The anode foil is expanded by forming the valve metal into a sintered body or an etched foil, and has a dielectric oxide film on the expanded surface. An electrolyte is present between the anode foil and the cathode foil. The electrolyte is in close contact with the concave and convex surface of the anode foil and functions as a true cathode.

[0003] In recent years, solid electrolytic capacitors using solid electrolytes containing conductive polymers such as polypyrrole, polyaniline, and polythiophene have begun to be used. Since conductive polymers have high electrical conductivity, they contribute to lowering the equivalent series resistance (ESR) of electrolytic capacitors.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2007 / 091656 Summary of the invention

[0007] Problems to be solved by the invention

[0008] Compared with solid electrolytes using conductive polymers, electrolytes can be in close contact with the dielectric oxide film layer of the anode foil, so it is easy to increase the capacitance of electrolytic capacitors. Therefore, electrolytic capacitors using conductive polymers are also required to have good ESR and good electrostatic capacitance.

[0009] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an electrolytic capacitor having better capacitance while using a conductive polymer and a method for producing the same.

[0010] Technical means of solving problems

[0011] In order to solve the above problems, the electrolytic capacitor of the present embodiment includes an electrolyte layer containing a conductive polymer and a flexible crystal, and may also include an anode body and a cathode body.

[0012] The conductive polymer may include poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid.

[0013] The soft and viscous crystal may further contain cations and anions in a combination different from the cation components and anion components of the soft and viscous crystal.

[0014] When the amount of the conductive polymer is set to 1, the amount of the flexible viscous crystal may be 2 times or more and 12 times or less in weight ratio.

[0015] In addition, in order to solve the above-mentioned problem, the manufacturing method of the electrolytic capacitor of the present embodiment includes an electrolyte layer forming process of forming an electrolyte layer between a pair of electrodes, and the electrolyte forming process has: a polymer attachment process of attaching a conductive polymer to one or both of the pair of electrodes; and a flexible and sticky crystal attachment process of attaching flexible and sticky crystals to one or both of the pair of electrodes.

[0016] The polymer attaching step may include an impregnation step of impregnating a liquid containing the conductive polymer between the pair of electrodes.

[0017] In the flexible and viscous crystal attaching step, the flexible and viscous crystal including cations and anions of a different combination from the cation components and anion components of the flexible and viscous crystal may be attached.

[0018] In the flexible viscous crystal attaching step, the flexible viscous crystal may be attached in an amount of 2 to 12 times by weight when the amount of the conductive polymer is 1.

[0019] Effects of the Invention

[0020] According to the present invention, better capacitance can be obtained compared with the case where a conductive polymer is used. DETAILED DESCRIPTION

[0021] Hereinafter, the embodiment of the present invention will be described. In addition, the present invention is not limited to the embodiment described below.

[0022] (Overall structure)

[0023] An electrolytic capacitor is a passive component that obtains electrostatic capacitance through the dielectric polarization of a dielectric oxide film and performs charge storage and discharge. An electrolytic capacitor includes a pair of electrodes and an electrolyte layer sandwiched by the electrodes. One of the electrodes is an anode body, and a dielectric oxide film is formed on the surface. The other electrode is a cathode body. The electrolyte layer contains conductive polymers and soft and viscous crystals.

[0024] Conductive polymers are self-doped conjugated polymers doped with intramolecular dopant molecules, or conjugated polymers doped with external dopant molecules. Conjugated polymers are obtained by chemical oxidation polymerization or electrolytic oxidation polymerization of monomers or derivatives having π conjugated double bonds. Dopant or external dopant molecules are acceptors that easily accept electrons from conjugated polymers, or donors that easily donate electrons to conjugated polymers, thereby making conductive polymers exhibit high conductivity.

[0025] Soft and sticky crystals are also called plastic crystals, and have ordered arrangement and disordered orientation. That is, soft and sticky crystals have a three-dimensional lattice structure in which anions and cations are regularly arranged, while these anions and cations have rotational irregularity.

[0026] The electrolyte layer containing these conductive polymers and soft and viscous crystals is interposed between the anode body and the cathode body. In other words, the anode body and the cathode body are arranged facing each other with the electrolyte layer interposed therebetween. The electrolyte layer is in close contact with the dielectric oxide film of the anode body and is arranged in a manner connected to the dielectric oxide film and the cathode body, thereby forming a conductive path and functioning as a true cathode.

[0027] The anode body and the cathode body are arranged in a stacked type in which the electrolyte layer is alternately stacked, or in a wound type in which the electrolyte layer is alternately stacked and wound. In the stacked type, in addition to being a flat plate type in which the outer cover is omitted, the capacitor element is sealed by, for example, covering it with a laminate film, or molding, dipping or printing a resin such as a heat-resistant resin or an insulating resin.

[0028] Alternatively, the anode body and the cathode body are alternately stacked and wound with the electrolyte layer interposed therebetween in a winding configuration. In the winding type, for example, the capacitor element is inserted into a bottomed cylindrical outer casing, and the open end of the outer casing is sealed by riveting and using a sealing body. The sealing body, for example, includes rubber, or a laminate of rubber and a hard substrate. Examples of the rubber include ethylene propylene rubber and butyl rubber.

[0029] In addition, a separator is included between the anode body and the cathode body to prevent short circuit between the anode body and the cathode body, the separator is used to separate the anode body from the cathode body and to maintain the electrolyte layer between the anode body and the cathode body. In the case where the shape of the electrolyte layer is maintained by itself and the cathode body and the anode body can be separated by the electrolyte layer, the separator can be excluded from the electrolytic capacitor.

[0030] (Anode)

[0031] In this type of electrolytic capacitor, the anode body is a foil body made of valve metal. In a wound type electrolytic capacitor, the valve metal is stretched into a long strip shape, and in a stacked type electrolytic capacitor, a sintered body is formed by molding a flat plate or powder into a flat plate shape and sintering it. Valve metals include aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Regarding purity, the anode body is ideally 99.9% or more, and may also contain impurities such as silicon, iron, copper, magnesium, and zinc.

[0032] A surface expansion layer is formed on one or both sides of the anode body. The surface expansion layer is an etching layer obtained by etching the foil, a sintering layer obtained by sintering valve metal powder, or a vapor-deposited layer obtained by vapor-depositing valve metal particles on the foil. That is, the surface expansion layer has a porous structure including tunnel-shaped pits, sponge-shaped pits, or gaps between dense powders or particles.

[0033] The tunnel-shaped etch pit is a hole dug in the thickness direction of the foil. The tunnel-shaped etch pit is typically formed by passing a direct current through an acidic aqueous solution such as hydrochloric acid in which halogen ions exist. The tunnel-shaped etch pit is further expanded by passing a direct current through an acidic aqueous solution such as nitric acid. Through the sponge-shaped etch pit, the expanded surface layer becomes a sponge-shaped layer that is expanded by connecting fine gaps into a space. The sponge-shaped etch pit is formed by passing an alternating current through an acidic aqueous solution such as hydrochloric acid in which halogen ions exist.

[0034] The sintered layer is made by the following method: a powder of a valve metal of the same or different species as the foil is obtained by a pulverization method, an atomization method, a melt spinning method, a rotating disk method, a rotating electrode method, etc., and a paste is made by using an adhesive or a solvent, applied to the foil and dried, and heated and sintered in a vacuum or a reducing environment. The atomization method can be any one of a water atomization method, a gas atomization method, and a water gas atomization method. The vapor-deposited layer is made, for example, by a resistance heating vapor deposition method or an electron beam heating vapor deposition method. The vapor-deposited layer is heated and evaporated by using resistance heat or electron beam energy to heat and evaporate the valve metal of the same or different species as the foil, so that the vapor of the valve metal particles is deposited on the surface of the foil to form a film.

[0035] The dielectric oxide film is formed on one or both sides of the anode body on which the surface expansion layer is formed. The dielectric oxide film is typically an oxide film formed on the surface layer of the anode body. If the anode body is made of aluminum, it is an aluminum oxide layer that oxidizes the surface of the surface expansion layer. In the chemical conversion treatment for forming the dielectric oxide film, a voltage is applied to the anode body in a chemical conversion solution with a desired withstand voltage as a target. The chemical conversion solution is a solution without halogen ions, for example, a phosphoric acid-based chemical conversion solution such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion solution such as ammonium borate, and an adipic acid-based chemical conversion solution such as ammonium adipate.

[0036] The anode lead is connected to the anode body and is led out of the capacitor element. The capacitor element is a component of the anode body, cathode body, electrolyte layer and separator. The anode lead is connected to the anode body by suturing, cold welding, ultrasonic welding or laser welding.

[0037] (Cathode)

[0038] In the case of a wound electrolytic capacitor, the cathode body is preferably a foil body extended from a valve-acting metal. As for the cathode body, the purity is ideally 99% or more. A surface expansion layer is formed on the cathode body in the same manner as the anode body. A flat foil without a surface expansion layer may also be used as the cathode body. The cathode body may have a natural oxide film or a thin oxide film (about 1V to 10V) formed by chemical conversion treatment. The natural oxide film is formed by the reaction of the cathode body with oxygen in the air. Furthermore, in the cathode body, a layer containing metal nitrides, metal carbides, or metal carbonitrides may be formed by a vapor deposition method, or a layer containing carbon may also be formed on the surface.

[0039] Alternatively, in the case of a laminated electrolytic capacitor, the cathode body is preferably a laminate of a metal layer and a carbon layer. The carbon layer of the cathode body is arranged toward the anode body. The carbon layer is formed by applying a paste to the electrolyte layer after forming an electrolyte layer on the anode body and hardening it by heating. The metal layer is, for example, a silver layer, and the metal layer is formed by applying a paste to the carbon layer and hardening it by heating.

[0040] The cathode lead is connected to the cathode body and is led out of the capacitor element. The cathode lead is connected to the cathode body by suturing, cold welding, ultrasonic welding or laser welding.

[0041] (Electrolyte layer)

[0042] (Conductive polymer)

[0043] As the conjugated polymer, known polymers can be used without particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylene vinylene, polyacene, polythiophene vinylene, etc. can be mentioned. These conjugated polymers can be used alone, or in combination of two or more, and can also be copolymers of two or more monomers.

[0044] Among the conjugated polymers, a conjugated polymer obtained by polymerizing thiophene or its derivatives is preferred, and a conjugated polymer obtained by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxin), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof is preferred. As a thiophene derivative, a compound selected from thiophenes having substituents at the 3- and 4-positions is preferred, and the substituents at the 3- and 4-positions of the thiophene ring can form a ring together with the carbons at the 3- and 4-positions. The number of carbon atoms in the alkyl or alkoxy group is preferably 1 to 16.

[0045] In particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, that is, poly(3,4-ethylenedioxythiophene) called PEDOT is particularly preferred. In addition, a substituent may be added to 3,4-ethylenedioxythiophene. For example, an alkylated ethylenedioxythiophene to which an alkyl group having 1 to 5 carbon atoms is added as a substituent may be used. Examples of the alkylated ethylenedioxythiophene include methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), butylated ethylenedioxythiophene (i.e., 2-butyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), and 2-alkyl-3,4-ethylenedioxythiophene.

[0046] The dopant may be a known one without particular limitation. The dopant may be used alone or in combination of two or more. In addition, a polymer or a monomer may be used. For example, as a dopant, inorganic acids such as polyanions, boric acid, nitric acid, and phosphoric acid; organic acids such as acetic acid, oxalic acid, citric acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalylboric acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid may be cited.

[0047] The polyanion is, for example, a substituted or unsubstituted polyalkylene, a substituted or unsubstituted polyalkenylene, a substituted or unsubstituted polyimide, a substituted or unsubstituted polyamide, or a substituted or unsubstituted polyester, and examples thereof include a polymer containing only a structural unit having an anionic group, and a polymer containing a structural unit having an anionic group and a structural unit not having an anionic group. Specifically, examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly(2-acrylamide-2-methylpropanesulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid.

[0048] The conductive polymer is produced by chemical oxidation polymerization or electrolytic oxidation polymerization. In chemical oxidation polymerization, a solution of monomers that become monomer units of the conductive polymer is mixed with an oxidant and subjected to polymerization reaction. As an oxidant, if it is a compound that releases a dopant, it can be any known one, and trivalent iron salts such as iron (III) p-toluenesulfonate, iron (III) naphthalenesulfonate, and iron (III) anthraquinonesulfonate, or peroxodisulfate salts such as peroxodisulfuric acid, ammonium peroxodisulfate, and sodium peroxodisulfate can be used. A single compound can be used, or two or more compounds can be used. There is no strict restriction on the polymerization temperature, but it is generally in the range of 10°C to 200°C. The polymerization time is generally in the range of 10 minutes to 30 hours.

[0049] In the electrolytic oxidation polymerization, the monomers that will become the monomer units of the conductive polymer are mixed with a supporting electrolyte and the polymerization reaction is carried out by constant potential method, constant current method or potential scanning method. The supporting electrolyte contains at least one compound selected from the group consisting of borodisalicylic acid and borodisalicylate. As salts, there can be exemplified: alkali metal salts such as lithium salts, sodium salts, potassium salts, ammonium salts, alkylammonium salts such as ethylammonium salts and butylammonium salts, dialkylammonium salts such as diethylammonium salts and dibutylammonium salts, trialkylammonium salts such as triethylammonium salts and tributylammonium salts, tetraalkylammonium salts such as tetraethylammonium salts and tetrabutylammonium salts.

[0050] In the case of the constant potential method, the potential is preferably 1.0 V to 1.5 V with respect to the reference electrode, and in the case of the constant current method, it is preferably 1 μA / cm 2 ~10000μA / cm 2 The current value is preferably scanned at a rate of 5 mV / sec to 200 mV / sec in the range of 0 V to 1.5 V relative to the reference electrode when using a potential scanning method. The polymerization temperature is not strictly limited, but is generally in the range of 10°C to 60°C. The polymerization time is generally in the range of 10 minutes to 30 hours.

[0051] In chemical oxidation polymerization or electrolytic oxidation polymerization, the solvent of the monomer and the oxidant or the supporting electrolyte can dissolve the desired amount of monomer and supporting electrolyte, and the solvent that does not adversely affect the electrolytic oxidation polymerization can be used without particular limitation. For example, as a solvent, water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, cyclopentane, dimethylcyclopentane. These solvents can be used alone or in combination of two or more.

[0052] The conductive polymer is formed in the electrolytic capacitor by immersing the attachment object to which the conductive polymer is attached in a solution of a monomer that becomes a monomer unit of the conductive polymer and an oxidant or a supporting electrolyte and generating it by polymerization reaction. The attachment object includes at least an anode body. In addition to the anode body, one or both of the cathode body and the separator can also be used as the attachment object of the conductive polymer. In addition, the assembly assembled with the anode body, the cathode body and the separator, that is, the capacitor element, can also be used as the attachment object, immersed in a solution of a monomer that becomes a monomer unit of the conductive polymer and an oxidant or a supporting electrolyte, so that it undergoes a polymerization reaction.

[0053] In addition, the conductive polymer can also be formed in the electrolytic capacitor by using an impregnation method in which a conductive polymer liquid in which particles or powder of the conductive polymer are dispersed or dissolved is impregnated into the attachment object. The conductive polymer liquid is prepared by purifying the solution after chemical oxidation polymerization or electrolytic oxidation polymerization by ultrafiltration, cation exchange, anion exchange, etc., removing residual monomers or impurities, and dispersing them in the solution.

[0054] The solvent of the conductive polymer liquid can be any solvent that disperses or dissolves the conductive polymer, and is preferably water or a mixture of water and an organic solvent. Examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds.

[0055] As polar solvents, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, etc. can be listed. As alcohols, methanol, ethanol, propanol, butanol, etc. can be listed. As esters, ethyl acetate, propyl acetate, butyl acetate, etc. can be listed. As hydrocarbons, hexane, heptane, benzene, toluene, xylene, etc. can be listed. As carbonate compounds, ethylene carbonate, propylene carbonate, etc. can be listed. As ether compounds, dioxane, diethyl ether, etc. can be listed. As chain ethers, ethylene glycol dialkyl ethers, propylene glycol dialkyl ethers, polyethylene glycol dialkyl ethers, polypropylene glycol dialkyl ethers, etc. can be listed. As heterocyclic compounds, 3-methyl-2-oxazolidinone, etc. can be listed. As nitrile compounds, acetonitrile, glutaronitrile, methoxyacetonitrile, propionitrile, benzonitrile, etc. can be listed.

[0056] The pH of the conductive polymer liquid can be adjusted, and polyols and various additives can be added as needed. As pH adjusters, for example, ammonia water can be cited. As polyols, sorbitol, ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerol, polyoxyethylene glycerol, xylitol, erythritol, mannitol, dipentaerythritol, pentaerythritol, or a combination of two or more of these can be cited. Since the boiling point of polyols is high, even after the conductive polymer liquid is impregnated in the attachment object and dried, it will remain in the electrolyte layer, and the ESR reduction or withstand voltage improvement effect of the electrolytic capacitor can be obtained. As additives, for example, organic binders, surfactants, dispersants, defoamers, coupling agents, antioxidants, ultraviolet absorbers, etc. can be cited.

[0057] After the conductive polymer liquid is impregnated into the attachment object, the solvent is removed by a drying process. The temperature environment in the drying process is, for example, above 40°C and below 200°C, and the drying time is, for example, in the range of above 3 minutes and below 180 minutes. The drying process can be repeated multiple times. It is also possible to dry under a reduced pressure environment, for example, under a reduced pressure of above 5kPa and below 100kPa. The drying process can be divided into pre-drying and formal drying processes. In addition to dipping, the conductive polymer solution can also be applied by dropwise coating or spray coating.

[0058] (Soft and sticky crystals)

[0059] The types of the anion component and the cation component constituting the flexible viscous crystal are not particularly limited as long as they are not ionic liquids but are in a solid state within the target temperature range in which the electrolytic capacitor is used.

[0060] Examples of the anion component constituting the soft and viscous crystal include various amide anions, tris(trifluoromethanesulfonyl)methanide anions, various phosphate anions, various borate anions, various sulfone anions, tetrafluoroaluminate anions, mandelate anions, and benzoate anions.

[0061] In various amide anions, two hydrogen atoms of the NH2 anion are substituted by perfluoroalkylsulfonyl, fluorosulfonyl, or both. Various amide anions include, for example, linear amide anions, various bis(perfluoroalkylsulfonyl)amide anions, bis(fluorosulfonyl)amide anions, and various N-(fluorosulfonyl)-N-(perfluoroalkylsulfonyl)amide anions represented by the following chemical formula (1).

[0062] (Chemistry 1)

[0063]

[0064] In the chemical formula (1), n ​​and m are integers of 0 or more, and the number of carbon atoms may be arbitrary.

[0065] In the formula (1), if n and m are 1 or more, it is a bis(perfluoroalkylsulfonyl)amide anion. As the bis(perfluoroalkylsulfonyl)amide anion, specifically, there can be mentioned the bis(trifluoromethanesulfonyl)amide anion (Bis(Trifluoro methane Sulfonyl)Amide Anion) (TFSA anion) represented by the following chemical formula (2) and the bis(pentafluoroethylsulfonyl)amide anion (Bis(Pentafluoro EthylSulfonyl)Amide Anion) (BETA anion) represented by the following chemical formula (3).

[0066] (Chemistry 2)

[0067]

[0068] (Chemistry 3)

[0069]

[0070] Specific examples of the bis(perfluoroalkylsulfonyl)amide anion include (pentafluoroethylsulfonyl)trifluoromethanesulfonylamide anions represented by the following chemical formula (4) wherein n is 1 and m is 2 in the chemical formula (1).

[0071] (Chemistry 4)

[0072]

[0073] In the formula (1), when the group with 0 carbon atoms is a fluorosulfonyl group and n and m are 0, the bis(fluorosulfonyl)amide anion (FSA anion) is represented by the following formula (5).

[0074] (Chemistry 5)

[0075]

[0076] In the formula (1), when n is 0 and m is 1 or more, the anion is N-(fluorosulfonyl)-N-(perfluoroalkylsulfonyl)amide anion represented by the following chemical formula (6). As the N-(fluorosulfonyl)-N-(perfluoroalkylsulfonyl)amide anion, specifically, m is 1 and N-(fluorosulfonyl)-N-(trifluoromethanesulfonyl)amide anion represented by the following chemical formula (7) and m is 2 and N-(fluorosulfonyl)-N-(pentafluoroethylsulfonyl)amide anion represented by the following chemical formula (8) can be cited.

[0077] (Chemistry 6)

[0078]

[0079] (Chemistry 7)

[0080]

[0081] (Chemistry 8)

[0082]

[0083] In addition, various amide anions include a (perfluoroalkylsulfonyl)fluoroacetamide anion in which two hydrogen atoms of an NH2 anion represented by the following chemical formula (9) are substituted with a perfluoroalkylsulfonyl group and a fluoroacetyl group.

[0084] (Chemistry 9)

[0085]

[0086] In the chemical formula (9), n is an integer of 0 or more, and the number of carbon atoms may be arbitrary.

[0087] In addition, various amide anions include, for example, heterocyclic rings of five-membered rings and six-membered rings, including N,N-hexafluoro-1,3-disulfonylamide anion (CFSA anion) represented by the following chemical formula (10) and N,N-pentafluoro-1,3-disulfonylamide anion represented by the following chemical formula (11).

[0088] (Chemistry 10)

[0089]

[0090] (Chemistry 11)

[0091]

[0092] Tris(trifluoromethanesulfonyl)methanide anion (TFSM anion) is represented by the following chemical formula (12).

[0093] (Chemistry 12)

[0094]

[0095] The various phosphate anions are hexafluorophosphate anions (PF6 anions) represented by the following chemical formula (13) or various perfluoroalkylphosphate anions represented by the following chemical formula (14) in which a part of the fluorine atoms of PF6 are substituted by a fluoroalkyl group.

[0096] (Chemistry 13)

[0097]

[0098] (Chemistry 14)

[0099]

[0100] In the chemical formula (14), q is an integer greater than or equal to 1, and the number of carbon atoms may be arbitrary.

[0101] Specifically, a tris(pentafluoroethyl)trifluorophosphate anion (FAP anion) represented by the following chemical formula (15) can be mentioned.

[0102] (Chemistry 15)

[0103]

[0104] Various borate anions include tetrafluoroborate anions (BF4 anions) represented by the following chemical formula (16), and various perfluoroalkyl borate anions represented by the following chemical formula (17) in which a part of the fluorine atoms of the BF4 anions are substituted by fluoroalkyl groups. As various perfluoroalkyl borate anions, specifically, for example, mono(fluoroalkyl)trifluoroborate anions and bis(fluoroalkyl)fluoroborate anions can be listed.

[0105] (Chemistry 16)

[0106]

[0107] (Chemistry 17)

[0108]

[0109] In the formula, s is an integer greater than or equal to 0, t is an integer greater than or equal to 1, and the number of carbon atoms may be arbitrary.

[0110] In addition, various borate anions further include borate anions represented by the following chemical formula (18).

[0111] (Chemistry 18)

[0112]

[0113] In the formula, R1 and R2 are independently keto or benzyl groups with one hydrogen removed from the benzyl position, or R1 and R2 are carbon atoms in a common aromatic six-membered ring. In the formula, R3 and R4 are independently keto or benzyl groups with one hydrogen removed from the benzyl position, or R3 and R4 are carbon atoms in a common aromatic six-membered ring.

[0114] In the formula (18), when R1, R2, R3 and R4 are all keto groups, it is a bis(oxalato)borate anion (Bis(Oxalato)Borate Anion) (BoB anion) represented by the following chemical formula (18A).

[0115] (Chemical 18A)

[0116]

[0117] In addition, in the chemical formula (18), if R1 and R2 are carbon atoms constituting a common aromatic six-membered ring, and R3 and R4 are carbon atoms constituting a common aromatic six-membered ring, then it is a bis(catecholate)borate anion represented by the following chemical formula (18B).

[0118] (Chemical 18B)

[0119]

[0120] In the chemical formula (18), when R1 and R4 are benzyl groups in which one hydrogen atom at the benzyl position is removed, and R2 and R3 are keto groups, the bis(phenylethylate)borate anion is represented by the following chemical formula (18C).

[0121] (Chemical 18C)

[0122]

[0123] In addition, various borate anions further include borate anions represented by the following chemical formula (19).

[0124] (Chemistry 19)

[0125]

[0126] In the formula, R1 to R6 are independently keto or methylene. Alternatively, in the formula, any one of R1 or R3 is a keto or methylene group, and the combination of the other R1 and R2 or the combination of R2 and R3 is a common carbon atom of an aromatic six-membered ring. Furthermore, in the formula, any one of R4 or R6 is a keto or methylene group, and the combination of the other R4 and R5 or the combination of R5 and R6 is a common carbon atom of an aromatic six-membered ring. The aromatic six-membered ring may have one or four methyl groups, and the aromatic six-membered ring is part of a polycyclic aromatic ring having two or more aromatic rings such as a naphthalene ring.

[0127] In the formula (19), if R1 and R6 are keto groups, R2 and R3 are carbon atoms that constitute a common aromatic six-membered ring, and R4 and R5 are carbon atoms that constitute a common aromatic six-membered ring, it is a bis(salicylato)borate anion (BScB anion) represented by the following chemical formula (19A).

[0128] (Chemical 19A)

[0129]

[0130] In the chemical formula (19), when R1 and R6 are keto groups, R2 and R3 are carbon atoms constituting a common aromatic six-membered ring, R4 and R5 are carbon atoms constituting a common aromatic six-membered ring, and the two aromatic six-membered rings each have four methyl groups, it is a bis(tetramethylsalicylate)borate anion represented by the following chemical formula (19B).

[0131] (Chemistry 19B)

[0132]

[0133] In the formula (19), when R1 and R6 are keto groups, R2 and R3 are carbon atoms constituting a common aromatic six-membered ring, R4 and R5 are carbon atoms constituting a common aromatic six-membered ring, and the two aromatic six-membered rings each have a methyl group, it is a bis(methylsalicylato)borate anion (Bis(MethylSalicylato)Borate Anion) (BmScB anion) represented by the following chemical formula (19C).

[0134] (Chemical 19C)

[0135]

[0136] In the formula (19), when R1 and R6 are keto groups, R2 and R3 are carbon atoms constituting a common naphthalene ring, and R4 and R5 are carbon atoms constituting a common naphthalene ring, it is a bis(1-hydroxy-2-naphtholato)borate anion represented by the following chemical formula (20A), a bis(2-hydroxy-1-naphtholato)borate anion (Bis(2-hydroxy-1-naphtholato)Borate Anion) (BhNB anion) represented by the following chemical formula (20B), or a bis(3-hydroxy-2-naphtholato)borate anion represented by the following chemical formula (20C).

[0137] (Chemical 20A)

[0138]

[0139] (Chemical 20B)

[0140]

[0141] (Chemical 20C)

[0142]

[0143] Examples of various sulfone anions include alkylsulfonate anions represented by the following chemical formula (21) and various perfluoroalkylsulfonate anions represented by the following chemical formula (22).

[0144] (Chemistry 21)

[0145] C X H 2x+1 SO3 - …(twenty one)

[0146] In the chemical formula (21), x is an integer of 1 to 4.

[0147] (Chemistry 22)

[0148] C y F 2y+1 SO3 - …(twenty two)

[0149] In the chemical formula (22), y is an integer of 1 to 4.

[0150] Specifically, various perfluoroalkylsulfonate anions include trifluoromethanesulfonate anion in which y is 1 in the chemical formula (22), pentafluoroethylsulfonate anion in which y is 2 in the chemical formula (22), heptafluoropropanesulfonate anion in which y is 3 in the chemical formula (22), and nonafluorobutanesulfonate anion in which y is 4 in the chemical formula (22).

[0151] The tetrafluoroaluminate anion is represented by the following formula (23).

[0152] (Chemistry 23)

[0153]

[0154] The mandelic acid anion is represented by the following formula (24).

[0155] (Chemistry 24)

[0156]

[0157] The benzoate anion is represented by the following formula (25).

[0158] (Chemistry 25)

[0159]

[0160] Examples of the cationic component constituting the soft and sticky crystal include various quaternary ammonium cations, various pyrrolidinium cations, various piperidinium cations, various imidazolium cations, and various phosphonium cations.

[0161] Examples of the quaternary ammonium cation include tetraalkylammonium cations represented by the following chemical formula (26) and substituted with a linear alkyl group having any carbon number.

[0162] (Chemistry 26)

[0163]

[0164] In the formula, a, b, c and d are integers greater than or equal to 1, and the number of carbon atoms may be arbitrary.

[0165] In the chemical formula (26), when a, b, c and d are 2, they are tetraethylammonium cations (TEA cations) represented by the following chemical formula (27).

[0166] (Chemistry 27)

[0167]

[0168] In the chemical formula (26), when a, b and c are 2 and d is 1, it is a triethylmethylammonium cation (TEMA cation) represented by the following chemical formula (28).

[0169] (Chemistry 28)

[0170]

[0171] Examples of the quaternary ammonium cation include a pyrrolidinium cation represented by the following chemical formula (29) and having a five-membered ring to which a methyl group, an ethyl group or an isopropyl group is bonded.

[0172] (Chemistry 29)

[0173]

[0174] In the formula, R1 and R2 are methyl, ethyl or isopropyl.

[0175] Specific examples of the five-membered ring pyrrolidinium cation generalized by the chemical formula (29) include: N-ethyl-N-methylpyrrolidinium cation (P12 cation) represented by the following chemical formula (30), N-isopropyl-N-methylpyrrolidinium cation (P13iso cation) represented by the following chemical formula (31), and N,N-diethylpyrrolidinium cation (P22 cation) represented by the following chemical formula (32).

[0176] (Chemistry 30)

[0177]

[0178] (Chemistry 31)

[0179]

[0180] (Chemistry 32)

[0181]

[0182] Examples of the quaternary ammonium include a spiro pyrrolidinium cation (SBP cation) represented by the following chemical formula (33).

[0183] (Chemistry 33)

[0184]

[0185] Various piperidinium cations are represented by the following chemical formula (34), and examples thereof include piperidinium cations in which a methyl group, an ethyl group or an isopropyl group is a six-membered ring.

[0186] (Chemistry 34)

[0187]

[0188] In the formula, R3 and R4 are methyl, ethyl or isopropyl.

[0189] Specific examples of the six-membered piperidinium cation generalized by the chemical formula (34) include, for example, a 1-ethyl-1-methylpiperidinium cation represented by the following chemical formula (35) in which R1 is a methyl group and R2 is an ethyl group.

[0190] (Chemistry 35)

[0191]

[0192] The various imidazolium cations are 1,3-dialkylimidazolium or 1,2,3-trialkylimidazolium cations represented by the following chemical formula (36).

[0193] (Chemistry 36)

[0194]

[0195] In the formula, h and i are integers of 1 to 3, and j is 0 or 1.

[0196] In the formula (36), when j is 0, h and i are 1, the 1,3-dimethyl imidazolium cation (DMI cation) represented by the following formula (37) is obtained. The 2-position of the DMI cation may be substituted with a methyl group.

[0197] (Chemistry 37)

[0198]

[0199] In the formula (36), if j is 0, h is 1 and i is 2, the 1-ethyl-3-methylimidazolium cation (EMI cation) represented by the following formula (38) is obtained. The 2-position of the EMI cation may be substituted by a methyl group.

[0200] (Chemistry 38)

[0201]

[0202] In the formula (36), when j is 0, h is 1 and i is 3, the 1-Methyl-3-Propyl Imidazolium Cation (MPI cation) represented by the following formula (39) is obtained. The 2-position of the MPI cation may be substituted with a methyl group.

[0203] (Chemistry 39)

[0204]

[0205] Examples of various phosphonium cations include tetraalkylphosphonium cations represented by the following chemical formula (40) and substituted with a linear alkyl group having any carbon number. Examples of tetraalkylphosphonium cations include tetraethylphosphonium cation (TEP cation).

[0206] (Chemistry 40)

[0207]

[0208] In the formula, e, f, g and h are integers greater than or equal to 1, and the number of carbon atoms may be arbitrary.

[0209] The electrolyte layer may contain two or more of such soft and sticky crystals. If two or more anionic components that can form soft and sticky crystals are mixed and used in the electrolyte layer, the ionic conductivity of the electrolyte layer is improved compared to the case where a single anionic component is used. In addition, if two or more cationic components that can form soft and sticky crystals are mixed and used in the electrolyte layer, the ionic conductivity of the electrolyte layer is improved compared to the case where a single cationic component is used.

[0210] When two or more flexible viscous crystals are included, the electrolyte layer may include flexible viscous crystals of the same anion, the same cation, or different anion and cation components. The different flexible viscous crystals may be mixed in equal molar amounts or in different amounts in the electrolyte layer.

[0211] In addition, the viscous crystal may contain cations and anions of a combination different from the cation components and anion components of the viscous crystal. The cations and anions contained in the viscous crystal can be ionized within the operating temperature range of the electrolytic capacitor. Such cations and anions can be contained in the viscous crystal in the form of an ionic liquid, for example. An ionic liquid is a salt that exists in a liquid state within a temperature range including room temperature, and is a liquid containing only ions.

[0212] If the anions contained in the flexible and sticky crystals are different, the cations contained in the flexible and sticky crystals may be the same as the cationic components constituting the flexible and sticky crystals. If the cations contained in the flexible and sticky crystals are different, the anions contained in the flexible and sticky crystals may be the same as the anionic components constituting the flexible and sticky crystals. The cations contained in the flexible and sticky crystals are of different species from the cationic components constituting the flexible and sticky crystals, and further, the anions contained in the flexible and sticky crystals may be of different species from the anionic components constituting the flexible and sticky crystals.

[0213] Examples of such anions include various amide anions of the above chemical formulas (1) to (25), tris(trifluoromethanesulfonyl)methanide anions, various phosphate anions, various borate anions, various sulfone anions, tetrafluoroaluminate anions, mandelate anions, and benzoate anions. Examples of cations include various quaternary ammonium cations of the above chemical formulas (26) to (40), various pyrrolidinium cations, various piperidinium cations, various imidazolium cations, and various phosphonium cations.

[0214] The content of cations and anions in a combination different from the cation components and anion components of the viscous crystal is not limited if no fluidity is observed in the viscous crystal by visual observation and the crystal becomes a solid state. By containing cations and anions in a combination different from the cation components and anion components of the viscous crystal, the ion conductivity of the electrolyte layer is further improved. The mixing ratio of cations and anions in a combination different from the cation components and anion components of the viscous crystal can be equimolar or different. Preferably, if the mixing ratio of the ionic liquid is 60wt% or less, the viscous crystal is easy to maintain a solid shape.

[0215] Polymers can be further added to the soft and sticky crystals to make them. Examples of polymers include polyethylene oxide (PEO), polypropylene oxide, polyester or carbonate polymers. Examples of carbonate polymers include polyethylene carbonate (PEC), derivatives of PEC, polypropylene carbonate, polytrimethylene carbonate, or copolymers of polytrimethylene carbonate and polycarbonate. One of these polymers can be used alone, or two or more can be used in combination.

[0216] Among these polymers, carbonate polymers are exemplified, and if they are aliphatic polycarbonates, they can all be used. In addition, when two or more are used in combination, various polymers can be in the form of single polymerization, or they can exist as copolymers of two or more monomers. The molecular weight of the polymer is not limited, and the molecular weight of the polymer is preferably more than 1000k. In addition, the molecular weight of polyethylene oxide (PEO) is preferably more than 1000k. By adding these polymers, the mechanical strength of the electrolyte layer can be improved, and in addition, the ionic conductivity of the electrolyte layer is improved.

[0217] The viscous crystals can be prepared, for example, by the following manufacturing method, but are not limited to the following, and various methods can be used. That is, the alkali metal salt of the anion component and the halogenated cationic component constituting the viscous crystals are dissolved in a solvent respectively. As alkali metals, Na, K, Li, and Cs can be listed. As halogens, F, Cl, Br, and I can be listed. As a solvent, water is preferably used. A solution of a metal salt of an anion is added dropwise to a solution of a halogenated cation and an ion exchange reaction is performed. An equimolar amount of a solution of a metal salt of an anion is added to a solution of a halogenated cation and stirred.

[0218] At this time, ion exchange generates soft and sticky crystals and generates alkali metal halides. If an organic solvent such as dichloromethane is mixed and left to stand, the mixed solution is divided into a water layer and a layer of the organic solvent. The alkali metal halides can be removed by removing the water layer from the liquid separation. The above operation can be repeated several times. Thus, after removing the alkali metal halides, the organic solvent such as dichloromethane is evaporated to obtain soft and sticky crystals.

[0219] The soft and sticky crystals are pre-dissolved in a solvent that can dissolve the soft and sticky crystals. The solvent is preferably a polar solvent. Examples of polar solvents include acetonitrile, propylene carbonate, γ-butyrolactone, dimethyl carbonate, ethyl methyl carbonate, ethylene carbonate, sulfolane, acetone, methanol, ethanol, isopropanol, or a mixture thereof. The soft and sticky crystals are efficiently dissolved in these polar solvents, so the productivity of the electrolyte layer is excellent.

[0220] Then, the solution of the soft viscous crystal is impregnated into the object to which the electrolyte layer is attached. After being impregnated with the solution of the soft viscous crystal, it is left to dry in a temperature environment such as 100°C where the solvent evaporates, thereby volatilizing the solvent and further volatilizing the water and the like remaining in the temperature environment such as 150°C. Thus, the soft viscous crystal is formed on the object to be attached.

[0221] In addition, the soft and sticky crystal may be doped with an ionic salt as an electrolyte. The ionic salt is a salt of an organic acid, a salt of an inorganic acid, or a salt of a composite compound of an organic acid and an inorganic acid, and may be used alone or in combination of two or more.

[0222] Examples of organic acids include oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, heptanoic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, tridecanedicarboxylic acid, and other carboxylic acids, phenols, and sulfonic acids. In addition, examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid containing tetrafluoroborate. Examples of composite compounds of organic acids and inorganic acids include boron disalicylic acid, boron dioxalic acid, and boron diglycolic acid.

[0223] Examples of at least one salt of the salts of these organic acids, inorganic acids, and composite compounds of organic acids and inorganic acids include ammonium salts, quaternary ammonium salts, quaternary amidinium salts, amine salts, sodium salts, potassium salts, and the like. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, and tetraethylammonium. Examples of quaternary amidinium include ethyldimethylimidazolinium and tetramethylimidazolinium. Examples of amines of amine salts include primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, and propylamine. Examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, and dibutylamine. Examples of tertiary amines include trimethylamine, triethylamine, tripropylamine, tributylamine, ethyldimethylamine, and ethyldiisopropylamine.

[0224] In addition, compared with a solid electrolytic capacitor that does not contain flexible viscous crystals and only contains conductive polymers, the capacitance of the electrolytic capacitor containing conductive polymers and flexible viscous crystals in the electrolyte layer is improved. In particular, the content of the flexible viscous crystals is preferably 2 times or more and 12 times or less relative to the content of the conductive polymer in terms of weight ratio. If the content of the flexible viscous crystals is 2 times or more relative to the content of the conductive polymer in terms of weight ratio, the electrostatic capacitance of the electrolytic capacitor is improved compared with a solid electrolytic capacitor that does not contain flexible viscous crystals and only contains conductive polymers, and the ESR is also reduced.

[0225] However, from the perspective of increasing electrostatic capacitance, the content of the flexible viscous crystals can be set to more than 12 times the weight ratio of the conductive polymer. Among them, in the flexible viscous crystal attachment process, a solution of the flexible viscous crystals is used, but if the content of the flexible viscous crystals is set to more than 12 times the weight ratio of the conductive polymer, the solubility of the flexible viscous crystals decreases, and simple dropwise impregnation becomes relatively difficult. On the other hand, by setting the content of the flexible viscous crystals to less than 12 times the weight ratio of the conductive polymer, the solubility of the flexible viscous crystals is improved. Therefore, by setting the content of the flexible viscous crystals to less than 12 times the weight ratio of the conductive polymer, the process of impregnating the solution of the flexible viscous crystals into the attachment object with the electrolyte layer attached becomes simple.

[0226] (Partition)

[0227] Examples of the separator include cellulose such as kraft paper, Manila hemp, esparto, hemp, rayon, and mixed papers thereof, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof, polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins, aliphatic polyamides, semi-aromatic polyamides, wholly aromatic polyamides, and other polyamide resins, polyimide resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, polyvinyl alcohol resins, and the like. These resins can be used alone or in combination.

[0228] (Method for manufacturing electrolytic capacitor)

[0229] (Wrapping type)

[0230] In this type of electrolytic capacitor, an example of the assembly process is shown for the winding type. First, a surface expansion layer is formed on one or both sides of the valve metal foil on the anode side, and a dielectric oxide film is formed on the surface expansion layer by chemical conversion treatment. A surface expansion layer is also formed on one or both sides of the valve metal foil on the cathode side as needed, and an oxide film is formed on the surface. For example, the anode lead and the cathode lead are pre-connected to the anode body and the cathode body by suturing, cold welding, ultrasonic welding or laser welding.

[0231] The long anode body and cathode body are wound with a separator interposed therebetween to form a cylindrical wound body. The separator is overlapped in a manner that one end thereof protrudes from one end of the anode body and the cathode body. The protruding separator is first wound so that the core of the wound body is along the short sides of the anode body and the cathode body to form a winding core. Then, the long sides of the anode body and the cathode body are rounded with the winding core as the winding axis.

[0232] A repair chemical conversion step is provided for repairing raw metal portions of the valve metal exposed when the anode and cathode bodies are cut to desired widths after winding, and defects of the anode and cathode bodies caused by physical stress such as winding.

[0233] In the repair chemical conversion process, the winding body is immersed in a chemical conversion liquid and a voltage is applied. As the chemical conversion liquid, a phosphoric acid-based chemical conversion liquid such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion liquid such as ammonium borate, adipic acid-based chemical conversion liquid such as ammonium adipate, or a chemical conversion liquid mixed with dicarboxylic acids such as boric acid and citric acid is used. The voltage is preferably set to a value of 0.1 to 1.2 times the chemical conversion voltage, for example. In addition, as a method of applying voltage during repair chemical conversion, it is appropriate to select a method of applying a certain voltage from the start of the repair chemical conversion, or a method of increasing the applied voltage in stages at certain intervals, etc.

[0234] Next, the electrolyte formation step is performed to form an electrolyte layer between the anode body and the cathode body. The electrolyte formation step is roughly divided into a polymer attachment step and a soft and sticky crystal attachment step. In the polymer attachment step, a conductive polymer is attached between the anode body and the cathode body, and in the soft and sticky crystal attachment step, a soft and sticky crystal is attached between the anode body and the cathode body.

[0235] In the polymer attachment process using the conductive polymer liquid, the winding body is immersed in the conductive polymer liquid so that the conductive polymer liquid is impregnated in the winding body. In order to promote the impregnation of the conductive polymer liquid in the winding body, a decompression treatment or a pressurization treatment may be performed as needed. The impregnation process may be repeated multiple times. After the conductive polymer liquid is impregnated in the winding body, the solvent of the conductive polymer liquid is removed by a drying process.

[0236] When the conductive polymer is attached while being generated, the wound body is immersed in a solution of a monomer that becomes a monomer unit of the conductive polymer and an oxidant or a supporting electrolyte to cause a polymerization reaction. After the conductive polymer is attached, the solvent is removed by a drying step.

[0237] Next, in the soft and sticky crystal attachment step, the wound body is immersed in the soft and sticky crystal solution so that the soft and sticky crystal solution is impregnated in the wound body. In order to promote the impregnation of the soft and sticky crystal solution in the wound body, a decompression treatment or a pressurization treatment may be performed as needed. The impregnation step may be repeated multiple times. After the soft and sticky crystal solution is impregnated in the wound body, the solvent is removed by a drying step.

[0238] On the wound body, the conductive polymer is first attached, and then the soft and sticky crystal is attached, but the soft and sticky crystal may be attached first, and then the conductive polymer is attached. Among them, from the viewpoint of forming a conductive path between the anode body and the cathode body, it is preferred to attach the conductive polymer first. By attaching the conductive polymer first, an electrolyte layer including the soft and sticky crystal and the conductive polymer layer can be uniformly formed, and good capacitance characteristics or good ESR characteristics can be exhibited.

[0239] Alternatively, in addition to the anode body, the conductive polymer and the soft adhesive crystal may be attached to the cathode body, the separator, or both, and then the anode body and the cathode body may be wound facing each other via a separator.

[0240] Regarding the capacitor element, the capacitor element is housed in an outer casing having a bottom at one end and an opening at the other end, and the capacitor element is sealed in the outer casing using a sealing body. Then, after the capacitor element is sealed in the outer casing, the electrolytic capacitor is completed through an aging process. In the aging process, a DC voltage is applied to the electrolytic capacitor to repair defective parts such as the dielectric oxide film layer.

[0241] (Laminated type)

[0242] In this type of electrolytic capacitor, an example of an assembly process is shown for a stacked type. First, a surface expansion layer is formed on the surface of a foil of a valve metal serving as an anode body. Next, the foil having the surface expansion layer formed thereon is subjected to a chemical conversion treatment in a chemical conversion solution to form a dielectric oxide film on the surface of the foil of the valve metal. Afterwards, an insulating resist layer is printed and dried, including the area serving as a terminal on the anode side, except for the area serving as an anode. That is, the insulating resist layer is printed in such a manner that an electrolyte layer is not formed in the area serving as a terminal on the anode side.

[0243] After the insulating resist layer is printed, the process is transferred to the conductive polymer attachment process, where the foil is immersed in a conductive polymer liquid to attach the conductive polymer in a manner that covers the dielectric oxide film. After the solvent of the conductive polymer liquid is removed by drying, the process is transferred to the soft viscous crystal attachment process, where the foil is immersed in a solution of soft viscous crystals to further attach the soft viscous crystals. Then, the solvent of the soft viscous crystals is removed by drying. The electrolyte layer is formed by the attachment of such conductive polymers and soft viscous crystals.

[0244] Next, a carbon paste is printed on the electrolyte layer using a screen printer and dried. The carbon layer is formed on the electrolyte layer through the drying process. Furthermore, a metal paste such as a silver paste is printed on the carbon layer and dried. After the drying process, a silver layer is formed on the carbon layer. These carbon layers and silver layers are equivalent to the cathode body of the electrolytic capacitor.

[0245] After the cathode body is formed, the insulating resist layer is peeled off. Alternatively, the insulating resist layer can be peeled off by mechanical peeling by laser irradiation or crimping with a clamp. The exposed portion due to peeling is plated to complete the anode terminal.

[0246] The capacitor element thus produced is covered with, for example, a laminate film, or is sealed by molding, dipping, or printing a resin such as a heat-resistant resin or an insulating resin.

[0247] Example

[0248] Hereinafter, the electrolytic capacitor and the method for manufacturing the same will be described in more detail based on examples. In addition, the present invention is not limited to the following examples.

[0249] (Example 1-Example 4)

[0250] The electrolytic capacitors of Examples 1 to 4 and Comparative Example 1 were fabricated as follows. First, a pair of electrodes were fabricated using aluminum foil. The two electrode foils were expanded by etching. One of the electrodes was set as an anode body and expanded by direct current etching. In the process of expanding the anode body, a direct current was passed through the aluminum foil in an aqueous solution containing hydrochloric acid to form pits, and then a direct current was passed through the aluminum foil in an aqueous solution containing nitric acid to expand the pits. The other electrode was set as a cathode body and expanded by alternating current etching. In the formation of the expanded layer of the cathode body, an alternating current was passed through the aluminum foil in an aqueous solution containing hydrochloric acid, thereby forming sponge-like etching pits.

[0251] The anode body was subjected to a chemical conversion treatment to form a dielectric oxide film on the surface of the foil. In the chemical conversion treatment step, a current density of 10 mA / cm was passed through an aqueous solution of ammonium dihydrogen phosphate with a concentration of 1.4 g / L and a liquid temperature of 90°C. 2 The current was increased to reach a chemical conversion voltage of 56.5 V and maintained for 10 minutes.

[0252] Lead wires were connected to each of the anode and cathode bodies, and the anode and cathode foils were wound with each other through a separator of Manila paper. The diameter of the wound body was 10 mm and the height was 10 mm. The wound body was energized for 10 minutes under the conditions of an applied voltage of 56.5 V and a current density of 10 mA in an aqueous solution of ammonium dihydrogen phosphate at a liquid temperature of 90°C, to perform a repair chemical conversion.

[0253] Initially, the winding body is impregnated with a conductive polymer liquid. The conductive polymer liquid is dispersed with poly(3,4-ethylenedioxythiophene) (PEDOT / PSS) doped with polystyrene sulfonic acid (PSS). PEDOT / PSS is added at a ratio of 1.2wt% relative to the conductive polymer liquid as a whole. In addition, ethylene glycol is added to the conductive polymer liquid at a ratio of 10wt% relative to the conductive polymer dispersion. The conductive polymer liquid is impregnated in the winding body for 10 minutes at room temperature and a pressurized environment of -0.3MPa. The impregnation process is performed twice in total.

[0254] After the wound body was pulled out from the conductive polymer liquid, it was left to stand at room temperature for 10 minutes and then left to stand at 110° C. for 30 minutes to dry. Thus, an electrolyte layer containing a conductive polymer was formed on the dielectric oxide film of the anode body.

[0255] Next, regarding Examples 1 to 4, in addition to the conductive polymer, a flexible and adhesive crystal was attached between the anode body and the cathode body. The flexible and adhesive crystals of Examples 1 to 4 are shown in Table 1 below.

[0256] (Table 1)

[0257]

[0258] As shown in Table 1, in Example 1, P12BF4 as a flexible crystal was attached. That is, a flexible crystal containing P12 cations and BF4 anions at a molar ratio of 1:1 was attached. The P12 cation was an N-ethyl-N-methylpyrrolidinium cation represented by the chemical formula (30).

[0259] In Example 2, P12FSA as a flexible crystal was attached. That is, a flexible crystal containing P12 cations and FSA anions at a molar ratio of 1:1 was attached. The FSA anion was a bis(fluorosulfonyl)amide anion represented by the chemical formula (5).

[0260] In Example 3, P12BoB as a flexible crystal was attached. That is, a flexible crystal containing P12 cations and BoB anions at a molar ratio of 1:1 was attached. The BoB anion was a bis(oxalate)borate anion represented by the chemical formula (18A).

[0261] In Example 4, P12BScB as a flexible crystal was attached. That is, a flexible crystal containing P12 cations and BScB anions at a molar ratio of 1:1 was attached. The BScB anion was a bis(salicylate)borate anion represented by the chemical formula (19A).

[0262] The viscous crystals were added to acetonitrile at a ratio of 40 wt % relative to the entire solution, and the acetonitrile solution was added dropwise to the wound body to impregnate the wound body with the acetonitrile solution. The impregnation amount was 570 mg relative to one wound body.

[0263] After impregnation, the wound body was allowed to stand for 2 hours in an argon environment at 45°C, for 2 hours in an argon environment at 60°C, for 2 hours in an argon environment at 80°C, and finally for 12 hours in an argon environment at 100°C, thereby drying the acetonitrile solution. Thus, in Examples 1 to 4, an electrolyte layer containing a conductive polymer and a flexible viscous crystal was formed. In Comparative Example 1, an electrolyte layer containing a conductive polymer and no flexible viscous crystal was formed.

[0264] The capacitor elements of Examples 1 to 4 and Comparative Example 1 were housed in an outer casing, and the opening of the outer casing was sealed with a sealing body. The sealing body and the outer casing were in close contact by riveting. Afterwards, an aging treatment was performed by applying a voltage of 40.25V for 1 hour to the electrolytic capacitors of Examples 1 to 6 and Comparative Example 1 at a temperature of 105°C. As a result, electrolytic capacitors with a diameter of 10mm and a height of 10mm, a rated voltage of 36WV and 270μF were produced.

[0265] The electrostatic capacitance (Cap), equivalent series resistance (ESR) and dielectric loss tangent (tanδ) of the electrolytic capacitors of Examples 1 to 4 and Comparative Example 1 were measured. Cap, tanδ and ESR were measured at room temperature using an inductance capacitance resistance (LCR) meter (manufactured by NF CORPORATION Co., Ltd., model ZM2376). The measurement frequency of Cap, ESR and tanδ was 120 Hz, and the AC current level was a sine wave of 1.0 Vms.

[0266] The measurement results of Cap, ESR, and tan δ of the electrolytic capacitors of Examples 1 to 4 and Comparative Example 1 are shown in Table 2 below.

[0267] (Table 2)

[0268]

[0269] As shown in Table 2, it was confirmed that the electrolytic capacitors of Examples 1 to 4 containing conductive polymers and flexible crystals in the electrolyte layer had improved capacitance compared to the conductive polymer solid electrolytic capacitor containing only conductive polymers without flexible crystals. In addition, the ESR and tanδ of the electrolytic capacitors of Examples 1 to 4 were also within the satisfactory range, and some examples were better than Comparative Example 1.

[0270] (Example 5-Example 6)

[0271] Electrolytic capacitors of Examples 5 and 6 were prepared. In Examples 5 and 6, the viscous crystal contained an ionic liquid. The structure, composition, preparation method, and preparation conditions of the electrolytic capacitors of Examples 5 and 6 were the same as those of the electrolytic capacitors of Examples 1 to 4, except that the viscous crystal contained an ionic liquid.

[0272] In Example 5, the viscous crystal is P12BF4 containing P12 cations and BF4 anions in a molar ratio of 1:1. The ionic liquid is EMIBF4 containing EMI cations and BF4 anions in a molar ratio of 1:1. The EMI cation is 1-ethyl-3-methylimidazolium represented by chemical formula (38). P12BF4 and EMIBF4 are prepared in equimolar amounts.

[0273] In Example 6, the viscous crystal is P12FSA containing P12 cations and FSA anions at a molar ratio of 1:1. The ionic liquid is EMIBF4 containing EMI cations and FSA anions at a molar ratio of 1:1. P12FSA and EMIFSA are prepared in equimolar amounts.

[0274] The electrostatic capacitance (Cap), equivalent series resistance (ESR) and dielectric loss tangent (tan δ) of the electrolytic capacitors of Examples 5 and 6 were measured under the same conditions as Examples 1 to 4 and Comparative Example 1. The measurement results of Cap, ESR and tan δ of the electrolytic capacitors of Examples 5 and 6 are shown in Table 3 below.

[0275] (Table 3)

[0276]

[0277] As shown in Table 3, when using a flexible crystal containing cations and anions in a different combination from the cation components and anion components of the flexible crystal, it can be confirmed that the capacitance is greatly improved compared with Comparative Example 1. In addition, it can be confirmed that the ESR and tanδ of the electrolytic capacitors of Examples 5 and 6 are significantly reduced compared with Comparative Example 1.

[0278] (Example 7-Example 9)

[0279] Electrolytic capacitors of Examples 7 to 9 and Comparative Example 2 were manufactured. The types of the flexible viscous crystals of the electrolytic capacitors of Examples 7 to 9 were different from those of Examples 1 to 4. The electrolytic capacitor of Comparative Example 2 was manufactured by the same manufacturing method as Comparative Example 1, except for the size of the winding body, and had the same structure. The winding bodies of Examples 7 to 9 and Comparative Example 2 were different from those of Examples 1 to 4 in that the diameter was 6.8 mm and the height was 5.8 mm.

[0280] In Example 7, P12BScB as a flexible crystal was attached. That is, a flexible crystal containing P12 cations and BScB anions at a molar ratio of 1:1 was attached. The BScB anion was a bis(salicylate)borate anion represented by the chemical formula (19A).

[0281] In Example 8, P12BmScB as a flexible crystal was attached. That is, a flexible crystal containing P12 cations and BmScB anions at a molar ratio of 1:1 was attached. The BmScB anion was a bis(methylsalicylate)borate anion represented by the chemical formula (19C).

[0282] In Example 9, TEABhNB as a flexible crystal was attached. That is, a flexible crystal containing TEA cations and BhNB anions at a molar ratio of 1:1 was attached. The TEA cation was a tetraethylammonium cation (TEA cation) represented by the chemical formula (27). The BhNB anion was a bis(2-hydroxy-1-naphtholate)borate anion represented by the chemical formula (20B).

[0283] The viscous crystals of Examples 7 and 8 are added to γ-butyrolactone in a ratio of 50 wt% relative to the whole solution. The viscous crystals of Example 9 are added to γ-butyrolactone in a ratio of 25 wt% relative to the whole solution. The γ-butyrolactone solution is added dropwise to the wound body so that the γ-butyrolactone solution is impregnated in the wound body. The γ-butyrolactone solution is impregnated for 30 minutes at room temperature and a reduced pressure environment of -80 kPa. At this time, -80 kPa is a gauge pressure based on atmospheric pressure, and the pressure represented by negative pressure is a gauge pressure based on atmospheric pressure.

[0284] After impregnation, the wound body was allowed to stand overnight at room temperature and a reduced pressure environment of -100 kPa or less, at 45°C and a reduced pressure environment of -100 kPa or less for 2 hours, at 60°C and a reduced pressure environment of -100 kPa or less for 2 hours, at 80°C and a reduced pressure environment of -100 kPa or less for 2 hours, and finally at 90°C and a reduced pressure environment of -100 kPa or less for one night, thereby fully drying the γ-butyrolactone solution and removing the γ-butyrolactone. Thus, in Examples 7 to 9, an electrolyte layer containing a conductive polymer and soft and sticky crystals was formed. In Comparative Example 2, an electrolyte layer containing a conductive polymer and no soft and sticky crystals was formed.

[0285] The electrostatic capacitance (Cap), equivalent series resistance (ESR), and dielectric loss tangent (tan δ) of the electrolytic capacitors of Examples 7 to 9 and Comparative Example 2 were measured. The measurement conditions were the same as those of Examples 1 to 4 and Comparative Example 1.

[0286] The measurement results of Cap, ESR, and tan δ of the electrolytic capacitors of Examples 7 to 9 and Comparative Example 2 are shown in Table 4 below.

[0287] (Table 4)

[0288]

[0289] As shown in Table 4, it was confirmed that the electrolytic capacitors of Examples 7 to 9 including conductive polymers and flexible crystals in the electrolyte layer had improved capacitance compared to the conductive polymer solid electrolytic capacitors containing only conductive polymers and not containing flexible crystals. The ESR and tanδ of the electrolytic capacitors of Examples 7 to 9 were also within the satisfactory range, and Example 7 was better than Comparative Example 2.

[0290] (Example 10-Example 14)

[0291] Electrolytic capacitors of Examples 10 to 14 and Comparative Example 3 were prepared. In Examples 10 to 14, P12BScB as a flexible crystal was attached, and the same manufacturing method as in Example 7 was used to prepare the capacitors, and the capacitors had the same structure. Comparative Example 3 was prepared by the same manufacturing method as in Comparative Example 1, and the capacitors had the same structure. The content of the conductive polymer and the content of the flexible crystal can be determined by measuring the weight before and after each attachment process, and the weight of the conductive polymer contained in the electrolytic capacitors of Examples 10 to 14 was 3 mg.

[0292] Among them, the weight ratio of the conductive polymer to the flexible viscous crystal of the electrolytic capacitor of Example 10 to Example 14 is different. In Example 10, the flexible viscous crystal is included in an amount of 0.2 times the weight ratio of the conductive polymer. In Example 11, the flexible viscous crystal is included in an amount of 1 times the weight ratio of the conductive polymer. In Example 12, the flexible viscous crystal is included in an amount of 2 times the weight ratio of the conductive polymer. In Example 13, the flexible viscous crystal is included in an amount of 5 times the weight ratio of the conductive polymer. In Example 14, the flexible viscous crystal is included in an amount of 12 times the weight ratio of the conductive polymer.

[0293] The electrostatic capacitance (Cap) and equivalent series resistance (ESR) of the electrolytic capacitors of Examples 10 to 14 and Comparative Example 3 were measured. Cap, tanδ and ESR were measured at room temperature using an LCR meter (manufactured by NF CORPORATION Co., Ltd., model ZM2376). The measurement frequency of Cap was 10 kHz, the measurement frequency of ESR was 100 kHz, and the AC current level was a sine wave of 1.0 Vms.

[0294] The measurement results of Cap and ESR of the electrolytic capacitors of Examples 10 to 14 and Comparative Example 3 are shown in Table 5 below.

[0295] (Table 5)

[0296]

[0297] As shown in Table 5 above, the electrolytic capacitors of Examples 10 to 14 have higher capacitance than Comparative Example 3. Furthermore, the ESR of the electrolytic capacitors of Examples 10 to 14 is also better than that of Comparative Example 3. Thus, it was confirmed that if the content of the flexible viscous crystal is 2 times or more and 12 times or less relative to the conductive polymer in terms of weight ratio, the electrolytic capacitor has high capacitance and good ESR.

Claims

1. An electrolytic capacitor, characterized in that: It includes an electrolyte layer containing a conductive polymer and a flexible and sticky crystal.

2. The electrolytic capacitor according to claim 1, characterized in that: The conductive polymer includes poly (3,4-ethylenedioxythiophene) and polystyrene sulfonic acid.

3. The electrolytic capacitor according to claim 1 or 2, characterized in that: The soft and viscous crystal further includes cations and anions in a combination different from the cation components and anion components of the soft and viscous crystal.

4. The electrolytic capacitor according to claim 1 or 2, characterized in that: When the amount of the conductive polymer is set to 1, the amount of the flexible viscous crystal is 2 times or more and 12 times or less in weight ratio.

5. A method for manufacturing an electrolytic capacitor, characterized in that: The electrolyte layer forming step includes forming an electrolyte layer between a pair of electrodes, The electrolyte forming step comprises: a polymer attachment step of attaching a conductive polymer to one or both of the pair of electrodes; and The flexible adhesive crystal attaching step attaches the flexible adhesive crystal to one or both of the pair of electrodes.

6. The method for manufacturing an electrolytic capacitor according to claim 5, characterized in that: One of the pair of electrodes is a foil of a valve metal, and is an anode body having a dielectric oxide film formed on the foil. The other of the pair of electrodes is a cathode body.

7. The method for manufacturing an electrolytic capacitor according to claim 5 or 6, characterized in that: The polymer attaching step includes an impregnation step of impregnating a liquid containing the conductive polymer between the pair of electrodes.

8. The method for manufacturing an electrolytic capacitor according to claim 5 or 6, characterized in that: In the flexible and viscous crystal attaching step, the flexible and viscous crystal including cations and anions of a different combination from the cation components and anion components of the flexible and viscous crystal is attached.

9. The method for manufacturing an electrolytic capacitor according to claim 5 or 6, characterized in that: In the flexible viscous crystal attaching step, the flexible viscous crystal is attached in an amount of 2 to 12 times by weight when the amount of the conductive polymer is 1.

Citation Information

Patent Citations

  • Conductive polymer solution, conductive coating, capacitor and process for manufacturing capacitor

    WO2007091656A1